Risk factors and outcome in dogs with recurrent massive hepatocellular carcinoma: A Veterinary Society of Surgical Oncology case–control study. (15th May 2022) - Lapsley, Janis M.; Wavreille, Vincent; Barry, Sabrina; Dornbusch, Josephine A.; Chen, Carolyn; Leeper, Haley; Bertran, Judith; Scavelli, Diane; Liptak, Julius M.; Wood, Chris; Shamir, Shelly; Rosenbaum, Claire; et al.
Abstract: Local recurrence after surgical excision of canine massive hepatocellular carcinoma (HCC) has been poorly studied in veterinary medicine with scant information published regarding risk factors for and outcome following recurrence. The aim of this case–control study was to describe the time to recurrence, evaluate potential risk factors for recurrence, and report the outcome in dogs with massive HCC. Medical records for 75 dogs who developed recurrence and 113 dogs who did not develop recurrence were reviewed. Statistical analyses were performed to determine risk factors for recurrence as well as the median time to develop recurrence and overall survival time (OS). None of the risk factors evaluated were significant for the development of recurrence. The median time to develop recurrence was 367 days (range 32–2096 days). There was no significant difference in median OS for dogs who developed recurrence vs. those who did not (851 vs. 970 days). For dogs with recurrent HCC, treatment at recurrence trended toward prolonged OS but was not significantly different from dogs not undergoing treatment at recurrence. There was no significant difference in median OS for dogs with histologically complete vs. incomplete tumour excision (990 vs. 903 days). Although specific risk factors for recurrence were not identified, elevations in liver values were noted in patients with recurrent disease and could act as a noninvasive surveillance tool. Recurrence was noted earlier in dogs who had routine post‐operative surveillance (228 vs. 367 days). Routine surveillance for recurrence is recommended especially in dogs where further intervention is possible and should extend beyond 1 year. Patients with massive HCC have a good long‐term prognosis regardless of incomplete excision, pulmonary metastasis, or recurrent local disease.